The Influence of Event Valence and Emotional States on the Metaphorical Comprehension of Time - Zheng, Weiqi; Liu, Ye; Liu, Chang Hong; Chen, Yu-Hsin; Cui, Qian; Fu, Xiaolan (Frontiers in Psychology, 2019)
Time is generally conceptualized in terms of space as reflected in temporal-spatial metaphors. Two observation perspectives have been proposed in the front-back axis of the temporal-spatial metaphor. One is called “ego-moving perspective” and the other “time-moving perspective”. They are used to represent different relative motion between time and the observer. Previous studies have demonstrated the psychological reality of both perspectives. They also provided evidence that emotion can influence a perspective choice. In general, a positive emotion tends to facilitate the adoption of ego-moving perspective whereas a negative emotion tends to promote the adoption of time-moving perspective. However, it is unclear how the motivational dimension of emotion might influence the preference. The current study aimed to address the question by identifying conditions in which emotional valence or motivational attribute affects the choice of time movement perspective. An ambiguous temporal question and a visualized time motion schema were adopted to probe participants’ metaphorical representation of time when they were affected by emotion. Study 1 investigated how a future emotional event would affect participants’ choice of the time movement perspective. The results showed that positive future events led to a higher propensity to adopt an ego-moving perspective compared with negative future events. Study 2 explored participants’ tendency to choose time movement perspective for a vague or neutral future event, after they were induced into a particular emotional state. The results showed that being in an emotional state of approach-motivation was more likely to adopt an ego-moving perspective. In contrast, being in an emotional state of avoidance-motivation, was more likely to take a time-moving perspective. Taken together, these results suggest that the emotional valence of future events can influence the choice of time movement perspectives; and the motivational dimension of present emotional states plays an important role when contemplating a neutral future event.